TRANSFORMASI DIGITAL PEMBELAJARAN PAI: PERAN BLENDED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA - Setiawan, Agus; Wahidah, Elya Maslichatul; Ilyasin, Mukhamad (STIT Ibnu Rusyd Tanah Grogot, 2025)
This study aims to analyze the effect of the blended learning model on the Islamic Education (PAI) learning outcomes of fifth-grade students at SD Islam Al Azhar 47 Samarinda. The background of the research is based on the importance of innovative learning approaches to improve learning outcomes, while the implementation of blended learning at the school has not yet been optimal. The method used is quantitative with a pre-test and post-test design involving 56 students. Data were collected through questionnaires, observations, and interviews, and then analyzed using normality tests, homogeneity tests, t-tests, and linear regression. Validity testing showed that 53 out of 60 items were valid, with the reliability coefficients for variable X (0.835) and variable Y (0.858), indicating that the research instruments are reliable. The trial results showed an increase in the average PAI score to 80.357. Normality and homogeneity tests confirmed that the data were normally distributed and homogeneous. The hypothesis test using the paired sample t-test resulted in a Sig. (2-tailed) value of 0.000 (< 0.05), indicating a significant effect. Meanwhile, the linear regression analysis showed a coefficient of determination (R²) of 0.446, meaning that 44.6% of the improvement in PAI learning outcomes was influenced by blended learning. The conclusion of this study proves that blended learning has a positive effect on students’ PAI learning outcomes. Its implication is that this model can be optimized as an innovative learning strategy in elementary schools. Recommendations for teachers and school administrators include enhancing technology training and providing supporting infrastructure to maximize the effectiveness of blended learning.